Uniaxial negative thermal expansion and metallophilicity in Cu3[Co(CN)6] - Sapnik, A; Liu, X; Boström, H; Coates, C; Overy, A; Reynolds, E; Tkatchenko, A; Goodwin, A (Elsevier, 2017)
We report the synthesis and structural characterisation of the molecular framework copper(I)hexacyanocobaltate(III), Cu3[Co(CN)6], which we ﬁnd to be isostructural to H3[Co(CN)6] and the colossalnegative thermal expansion material Ag3[Co(CN)6]. Using synchrotron X-ray powder diﬀraction measurements,we ﬁnd strong positive and negative thermal expansion behaviour respectively perpendicular and parallel to thetrigonal crystal axis:α= 25.4(5) MKa−1andα= − 43.5(8) MKc−1. These opposing eﬀects collectively result in avolume expansivityα= 7.4(11) MKV−1that is remarkably small for an anisotropic molecular framework. Thisthermal response is discussed in the context of the behaviour of the analogous H- and Ag-containing systems.We make use of density-functional theory with many-body dispersion interactions (DFT + MBD) todemonstrate that Cu+…Cu+metallophilic (‘cuprophilic’) interactions are signiﬁcantly weaker in Cu3[Co(CN)6]than Ag+…Ag+interactions in Ag3[Co(CN)6], but that this lowering of energy scale counterintuitively translatesto a more moderate—rather than enhanced—degree of structural ﬂexibility. The same conclusion is drawn fromconsideration of a simple GULP model, which we also present here. Our results demonstrate that stronginteractions can actually be exploited in the design of ultra-responsive materials if those interactions are set upto act in tension.